2018
DOI: 10.1097/jtn.0000000000000336
|View full text |Cite
|
Sign up to set email alerts
|

Improving Thermoregulation for Trauma Patients in the Emergency Department: An Evidence-Based Practice Project

Abstract: Extensive evidence exists on the association between hypothermia and increased morbidity and mortality in trauma patients. Gaps in practice related to temperature assessment have been identified in literature, along with limited personnel knowledge regarding management of patients with accidental hypothermia. An interdisciplinary team identified gaps in practice in our institution regarding temperature assessment and documentation of rewarming and initiated an evidence-based practice project to change practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…In this study, the mean value of the nurses' knowledge was significantly different after instructional intervention [30]. Saqe-Rockoff et al (2018) completed an evidence-based project on the improvement of the trauma patients' temperature regulation and reported that the implementation of an evidence-based instructional intervention improved the emergency nurses' performance in regard to patient thermal care [24]. Other studies have often focused on the inadequacy of the knowledge and performance of physicians, nurses, and the other people who are involved in trauma patient care and have emphasized the need to take effective measures to improve staff information and skills for the optimal management of hypothermia in these patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this study, the mean value of the nurses' knowledge was significantly different after instructional intervention [30]. Saqe-Rockoff et al (2018) completed an evidence-based project on the improvement of the trauma patients' temperature regulation and reported that the implementation of an evidence-based instructional intervention improved the emergency nurses' performance in regard to patient thermal care [24]. Other studies have often focused on the inadequacy of the knowledge and performance of physicians, nurses, and the other people who are involved in trauma patient care and have emphasized the need to take effective measures to improve staff information and skills for the optimal management of hypothermia in these patients.…”
Section: Discussionmentioning
confidence: 89%
“…Treatment strategies focus on prevention of heat loss, fluid resuscitation, and implementation of appropriate warming techniques and management of cardiac dysrhythmias [23]. Weaknesses in the assessment of patient's body temperature and limited staff knowledge of the management of patients with hypothermia have been identified in several studies [22,24,25]. Recording temperature in trauma patients is an essential requirement to help the physician make informed decisions to manage hypothermia and to evaluate the effectiveness of the rewarming method.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a lack of staff training on how to handle patients who have accidentally become hypothermic, gaps in practice relating to temperature assessment have been found in the literature. Rewarming techniques are employed in prehospital care to enhance patient outcomes and lessen the discomfort imposed by colds [6,27]. Therefore, in their work, physicians, nurses, and emergency paramedics must follow evidence-based guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…There is more data supporting the link between hypothermia and higher morbidity and death rates in trauma patients. Even mild hypothermia can greatly enhance morbidity in trauma victims [5,6]. The mortality rate in trauma patients is significantly increased by hypothermia combined with acidosis and coagulopathy [7].…”
Section: Introductionmentioning
confidence: 99%
“…A hipotermia é uma complicação que pode contribuir para a deterioração do quadro clínico dos pacientes hospitalizados, sendo uma urgência que requer rápida e eficaz intervenção do enfermeiro para o restabelecimento da normotermia, a fim de evitar maiores prejuízos ao paciente. Em unidades de emergência, a alta mortalidade está associada a acidentes, a hipotermia por exposição e lesões traumáticas graves, complicações como a coagulopatia e a acidose metabólica é considerada como "tríade letal" 1,2 .…”
Section: Introductionunclassified